Analyzing the Needs on Teaching Writing Materials in Promoting 21st Century Skills - Hendi Hidayat; Mutiara, Linda (STIT Buntet Pesantren Cirebon, 2023)
Needs analysis plays an important role in developing writing materials and tools that help teachers design materials according to the target needs and learning needs of students. This case is a challenge for teachers to develop writing materials to achieve learning targets according to 21 century skills. Thus the learning system applied by teachers in the 21st century will affect student achievement and learning styles. The purpose of this research was to analyze the types of students’ target and learning needs for the development of writing materials in promoting 21st century skills. According to Hutchinson and Waters (1987, pp. 55-56) target needs include: necessities, lacks, and wants. While learning needs includes: input, procedure, setting, and learners’ role. This research took an English teacher and some eleventh grade students at MAN 3 Cirebon. This research was conducted by using qualitative studies through case study design. Data collection of this research was interviews and document analysis. The data were analyzed, interpreted, and represented by researchers’ view. This research described how the targets and learning needs of students in teaching and learning to write in the 21st century.